Analisis Model Bisnis Budidaya Maggot Skala Komunitas Berbasis Circular Economy di Sumur Batu, Kota Bekasi - Sulastri .; Lisdiana; R. Sapto Yuwono (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
This study analyzes the business model of community-scale maggot cultivation based on a circular economy in RW 08, Sumur Batu Village, Bantargebang District, Bekasi City. The method used is a qualitative descriptive case study through structured interviews, observations, and documentation. The business unit is able to process 110 kg of organic waste per day and produce 10 kg of maggot and 1.5 kg of frass. The activity was carried out collectively by residents, with raw materials from the RW waste bank in partnership with the Patriot Main Waste Bank. The main products are fresh maggots, dried maggots, as well as solid and liquid frass fertilizers. The selling price is IDR 7,000/kg, IDR 80,000/kg, and IDR 15,000/kg, respectively. This business has a positive impact on the environment and economy, despite the constraints of limited human resources. This research contributes to the development of an applicable and sustainable circular business model for urban communities.